2021
DOI: 10.1038/s41598-021-95153-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the predictability of existing water-to-enamel geolocation models against known human teeth

Abstract: Stable isotope analysis of human tissues has become a valuable tool for mapping human geolocation. This study adds to the existing knowledge of the relationship between oxygen stable isotopes in human enamel and drinking water by presenting enamel oxygen values in clinic-extracted human dental enamel with known provenance. The results from this study indicate that the theoretical isotopic relationship between enamel and drinking water oxygen is weak at the city and country-level. Differences of up to 15‰ were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…Furthermore, it has been shown that isotopic variations in recently formed human tissues can exist for a single geographical area. The isotopic spread of δ 18 O values of enamel was 4‰ for Metro Vancouver in British Columbia, Canada 4 , and although explained by the large isotopic range of tap water that supplies the regional district 7 , the intrapopulation variation is larger than what has previously been estimated for any geographical region 8 , 9 . Thus, isotopic values obtained from a single tissue cannot represent the entire geographical area.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Furthermore, it has been shown that isotopic variations in recently formed human tissues can exist for a single geographical area. The isotopic spread of δ 18 O values of enamel was 4‰ for Metro Vancouver in British Columbia, Canada 4 , and although explained by the large isotopic range of tap water that supplies the regional district 7 , the intrapopulation variation is larger than what has previously been estimated for any geographical region 8 , 9 . Thus, isotopic values obtained from a single tissue cannot represent the entire geographical area.…”
Section: Introductionmentioning
confidence: 72%
“…δ 2 H and δ 18 O values for Metro Vancouver cities (Site 1) were taken from Ueda and Bell's 7 study on Metro Vancouver tap water. δ 2 H and δ 18 O values for each Metro Vancouver municipality were calculated by determining the fractional contribution of each water source to the main Metro Vancouver municipal water supply as outlined in Ueda and Bell 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aims to investigate whether stable carbon isotope values in human enamel bioapatite from Canada fall within any of the regional isotopic boundaries as liberally defined by Kamenov and Curtis [4], and whether Canadian can be distinguished from the combined analysis of stable carbon and oxygen isotopes for forensic human geolocation queries. Stable carbon isotope values were obtained from enamel samples with known geographical information that were collected as part of a stable oxygen isotope study by Ueda and Bell [46].…”
Section: Kamenov and Curtismentioning
confidence: 99%
“…Finally, Region 3 included individuals from Mexico, Central American, and South America with the highest δ 13 C values. Currently, there are no existing studies for stable carbon isotopes in human tooth enamel bioapatite, with only a single study for stable oxygen isotopes [46], and thus it is unclear whether Canadian samples will show consistent δ 13 C enamel values with any of the regions identified above. Canada shares an 8890-km land border [47] as well as a highly integrated food supply chain with the US [48] and therefore could show consistent values to those of US Americans.…”
Section: Adult Carbon Enamel Values Generally Reflect the Individual'smentioning
confidence: 99%